Meningkatkan Kompensasi, Kepuasan Kerja Dan Motivasi Untuk Mengurangi Labor Turnover Intention - Sumarto, Sumarto (Jurnal Riset Ekonomi dan Bisnis, 2009)
One of important aspect in organization is maintain existence of employee and push down turnover intention.Turnover intention is the result of the exit of some employees and entrance of others to the work organization. Turnover intention refers to the movement into and out of an organization by the work force. Turnover intention maybe define as any permanent departure beyond the organizational boundaries. Negative effect existence of turnover intention is the increasing of expense of recruitment. Other effect which more important is communications that's more and more ugly and organizational performance trouble. Base on reasoning of turnover intention problem this research purposed to analyses of relation between compensation, job satisfaction, motivation, and labor turnover intention.Base on research purpose, primary data be applied in this research. Research population are  employee of several company in Surabaya which consist of 450 employee. From 450 employees, as much 150 employee be created as sample, by using random sampling technique. This amount have been compatible with general agreement which can be analyzed by using SEM.Result of the research indicates that there are significant influence from : compensation to job satisfaction, compensation to negative motivation, motivation  to negative labor turnover intention, job satisfaction to motivation. There are two relationship which not significant, those are from : compensation to labor turnover intention, and job satisfaction to labor turnover intention. This result can be concluded that labor turnover intention can be reduced through : increasing compensation so job satisfaction will go up, then motivation also go up, and finaly  labor turnover intention go down.Keywords: Compensation, Job Satisfaction, Motivation,  Labor Turnover Intention